Hierarchical Cu/Cu(OH)2 nanorod arrays grown on Cu foam as a high-performance 3D self-supported electrode for enzyme-free glucose sensing. Issue 98 (7th October 2016) - Bie, Lili; Luo, Xue; He, Qingqing; He, Daiping; Liu, Yan; Jiang, Ping
Abstract : Hierarchical Cu/Cu(OH)2 nanorod arrays grown on Cu foam (Cu/Cu(OH)2 NRA/CF) were prepared via a three-step strategy involving the synthesis of Cu(OH)2 NRA/CF, the preparation of Cu NRA/CF, and the growth of Cu(OH)2 nanoparticles on Cu NRA/CF. Abstract : Hierarchical Cu/Cu(OH)2 nanorod arrays grown on commercially available Cu foam (Cu/Cu(OH)2 NRA/CF) was prepared via a three-step strategy involving the wet chemical synthesis of Cu(OH)2 NRA/CF, a chemical reduction reaction for conversion from Cu(OH)2 NRA/CF to Cu NRA/CF, and finally galvanostatic anodization to grow Cu(OH)2 nanoparticles on Cu NRA/CF. Hierarchical Cu/Cu(OH)2 NRA/CF shows high catalytic activity towards glucose oxidation in an alkaline solution and can serve as a promising electrode material for enzyme-free glucose sensing. At an applied potential of +0.5 V, the sensor showed a broad detection range of 0.001–1.0 mM, a high sensitivity of 9.18 mA mM −1 cm −2, and a low detection limit of 0.45 μM (S/N = 3). Furthermore, the sensor exhibits excellent selectivity against common interferents and good reliability for glucose detection in human serum samples.